2010
DOI: 10.1101/gad.1865810
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the YAP and TEAD complex

Abstract: The Yes-associated protein (YAP) transcriptional coactivator is a key regulator of organ size and a candidate human oncogene inhibited by the Hippo tumor suppressor pathway. The TEAD family of transcription factors binds directly to and mediates YAP-induced gene expression. Here we report the three-dimensional structure of the YAP (residues 50-171)-TEAD1 (residues 194-411) complex, in which YAP wraps around the globular structure of TEAD1 and forms extensive interactions via three highly conserved interfaces. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
528
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(557 citation statements)
references
References 41 publications
28
528
0
1
Order By: Relevance
“…The target specificity may be provided by the YAP1 portion of the fusion (Fig. 4A), which contains a domain that interacts with the pluripotency transcription factor TEAD1 (Li et al 2010). In particular, the YAP1-TEAD1 complex was demonstrated to bind promoters of many genes important for ES cells, which are also targets of polycomb group proteins, NANOG, POU5F1, and SOX2 (Lian et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The target specificity may be provided by the YAP1 portion of the fusion (Fig. 4A), which contains a domain that interacts with the pluripotency transcription factor TEAD1 (Li et al 2010). In particular, the YAP1-TEAD1 complex was demonstrated to bind promoters of many genes important for ES cells, which are also targets of polycomb group proteins, NANOG, POU5F1, and SOX2 (Lian et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the levels of pluripotency markers, such as Pou5f1 and Nanog, as well as various lineage markers were not significantly affected by either single or double KD of Yap1 and Taz (Fig 2C and D), indicating that the dispensability of Yap1 in self-renewing ES cells is not due to the compensatory effect of Taz. Since Yap1 is known to require Tead family proteins to activate its downstream target genes in NIH-3T3 and MCF10A cell lines [17,28,29], we investigated whether Tead proteins are also dispensable for the maintenance of ES cells. To do so, we first performed KD of Tead2 in ES cells.…”
Section: Taz and Tead Family Proteins Are Not Required For Self-renewmentioning
confidence: 99%
“…A homologue of Yap1, Taz, shares redundant functions such as controlling cell proliferation and sensing mechanical stress [14,15]. Furthermore, Tead proteins-important in TE differentiation during early embryogenesis, form a complex with Yap1 and are known to activate their downstream target genes [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The function of Sd-Yki complex has been intensively studied. In mammals, the structure and function of TEAD-YAP were well characterized [26][27][28]. Recent studies revealed that mammalian TEAD proteins are involved in the regulation of cell proliferation by cooperating with YAP under the control of Hpo signaling [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%